Spanish Orientalism of the 19th century. Mariano Fortuny - Chelovan, Anastasia E. (Actual Problems of Theory and History of Art, 2025)
Spanish art of the 19th century has been rarely explored by Russian scholars. In the present article the author studies Oriental motives in M. Fortuny's works, derived from the Spanish national art and the Europen Orientalism.
Keywords: Spain; 19th century; Mariano Fortuny; Romanticism; Orientalism